Ser14 phosphorylation of Bcl-xL mediates compensatory cardiac hypertrophy in male mice - Michinari Nakamura; Mariko Aoyagi Keller; Nadezhda Fefelova; Peiyong Zhai; Tong Liu; Yimin Tian; Shohei Ikeda; Dominic P. Del Re; Hong Li; Lai-Hua Xie; Junichi Sadoshima (Nature Communications, 2023)
Abstract The anti-apoptotic function of Bcl-xL in the heart during ischemia/reperfusion is diminished by K-Ras-Mst1-mediated phosphorylation of Ser14, which allows dissociation of Bcl-xL from Bax and promotes cardiomyocyte death. Here we show that Ser14 phosphorylation of Bcl-xL is also promoted by hemodynamic stress in the heart, through the H-Ras-ERK pathway. Bcl-xL Ser14 phosphorylation-resistant knock-in male mice develop less cardiac hypertrophy and exhibit contractile dysfunction and increased mortality during acute pressure overload. Bcl-xL Ser14 phosphorylation enhances the Ca2+ transient by blocking the inhibitory interaction between Bcl-xL and IP3Rs, thereby promoting Ca2+ release and activation of the calcineurin-NFAT pathway, a Ca2+-dependent mechanism that promotes cardiac hypertrophy. These results suggest that phosphorylation of Bcl-xL at Ser14 in response to acute pressure overload plays an essential role in mediating compensatory hypertrophy by inducing the release of Bcl-xL from IP3Rs, alleviating the negative constraint of Bcl-xL upon the IP3R-NFAT pathway.